OP65 A cross-sectional study of the relationship between wealth, social participation and loneliness among older people across Europe. (13th September 2016) - Niedzwiedz, C; Richardson, E; Tunstall, H; Shortt, N; Mitchell, R; Pearce, J
Abstract : Background: Loneliness is an increasing public health concern as longevity increases across European societies. This study examines the relationship between household wealth and loneliness among individuals aged 65+ years who were not currently in the paid labour force. Further, we investigate whether social participation acts as a moderating factor between household wealth and loneliness and if differences are apparent according to the type of social participation (charity or volunteer work, sports or social clubs, educational or training course, and political or community organisation). Methods: Data were taken from the fifth wave of the Survey of Health, Ageing and Retirement in Europe (SHARE), which was conducted during 2013 and included a representative sample of non-institutionalised individuals aged 50+ years from 14 European countries (Austria, Belgium, Switzerland, Czech Republic, Germany, Denmark, Estonia, Spain, France, Italy, Luxembourg, Netherlands, Sweden and Slovenia). Loneliness was measured using the short version of the R-UCLA Loneliness Scale and scores ranged from 3 to 9, whereby 9 indicated the highest level of loneliness. We used multilevel linear models stratified by gender to examine the relationships between variables, with individuals nested within countries. Average marginal effects of social participation on loneliness were calculated by household wealth quintile and Wald tests were used to test for statistical interactions. Results: Loneliness scores were lowest in the wealthiest groups and highest in the least wealthy groups. Social participation was associated with lower loneliness scores and moderated the association between household wealth and loneliness among men, but not women. The average marginal effect of frequent social participation on loneliness for men in the least wealthy quintile was −0.35 (95% CI: −0.48 to −0.22), whereas in the wealthiest quintile it was −0.02 (95% CI: −0.12 to 0.09). The strength of the association between social participation and loneliness was strongest for participation in sports or social clubs and charity or volunteer work. The potential moderating effect of social participation on loneliness was specific to men's participation in sports and social clubs. Conclusion: Loneliness is socially patterned in old age, echoing other observed social inequalities in health and wellbeing. Participation in specific social activities may help to reduce loneliness among older adults and potentially acts as a buffer against the adverse effects of socioeconomic disadvantage among men, but longitudinal evidence is needed. The key limitations of our study include its cross-sectional study design and the exclusion of institutionalised individuals.